Evaluation of the perception of breastfeeding reported by lactating women compared to the LATCH in a maternal and child ward at the University Hospital of Western Paraná (Research, Society and Development, 2023)
Breastfeeding is a key factor for the development and growth of the baby, especially in the first six months of life. When addressing issues about breastfeeding and early weaning, there are relevant factors such as nipple trauma, as it will directly result in breastfeeding. The objective of the study was to evaluate the perception of breastfeeding reported by lactating women and compare it with the LACTH questionnaire, in a sample of infants from a maternal and child ward at the University Hospital of Western Paraná. The present research is a cross-sectional study, developed with newborns born at the Maternity Hospital of the West of Paraná University Hospital - HUOP, from June to September 2022, with the application of the LATCH questionnaire and a guided interview. The final sample of this research consisted of 82 live newborns of both sexes and gestational age ≥ 37 weeks. With regard to newborns who presented breastfeeding difficulties, there was a significance level (p = 0.0029). Isolated factors can comprise the adaptation phase during breastfeeding, but the difficulties must be resolved, as a means of strengthening the maternal bond with the newborn. It is concluded that newborns without difficulty had a significantly higher LATCH.